MODERN TECHNOLOGY IN THE MEDIA BUSINESS - Nadezda M. Salnikova (Статистика и экономика)
The article reviews the features of modern technologies in media culture and business - by the example of computer games. A classification of the Russian computer game market in its various segments and the general description of the development and its features. The proposed classification reveals the innovative features of the development of this sector, as a segment of the secondary market in the film industry, to identify opportunities for additional revenue from the sale of film production. This type of media is under active development in Russia, but it was not paid by the due attention of researchers.